Best Answer

Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?

Study guides

☆☆

Q: How do you simplify 6a plus 2b-3a plus 5b?

Write your answer...

Submit

Still have questions?

Continue Learning about Movies & Television

6a to the second power minus 8ab + 2a

6a

2 x 3 x a = 6a

With the assumption your asking what a or b are in terms of each other. a=3b/(6b-2) b=2a/(6a-2)

6a

Related questions

3a + 5b - 6a - 9b = -3a - 4b

(4, 3)

2a² + 6a

It is equivalent to 53a+44b when simplified

4(5b - 6a^2)(5b + 6a^2)

It is 9

the answer

It is 20a - 5b - 9.

a = 1/2

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

11a+7b-(3b-2a)

21a - 6a

People also asked

Featured Questions